Формализация многоагентных систем с помощью теории паттернов - Маторин, С. И.; Михелев, М. В. (НТУ "ХПИ", 2008)
В статье рассмотрены многоагентные системы (МАС) и теория паттернов. Предложена модель, позволяющая формализовать структурную и функциональную часть агента. Также представлено описание МАС в виде алгебраической системы.

In article multiagent systems (MAS) and the theory of patterns are considered. It suggested allowing to formalize a structural model and functional part of the agent. Also description MAS in the form of algebraic systemis presented.
Formalization of the multiagent systems by the theory of patterns
Keywords: агент; МАС; УФО-элемент; алгебраическая система; уровень интеллектуальности; agent